Pengembangan Local Stories Book untuk Siswa Kelas 1 Sekolah Dasar Kecamatan Singorojo Kabupaten Kendal - Ningrum, Tyas; Widayati, Sri; Wijayanti, Atrianing Yessi (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2024)
This research aims to develop a local stories book in Indonesian language subjects for grade 1 elementary school students in Singorojo District, Kendal Regency. This research also aims to determine the validity and practicality of the local stories book which was developed according to students' needs. This research uses a development model according to Sugiyono which includes potential and problems, data collection, product design, design validation, design improvement, product testing, and product revision. The data analysis techniques used are quantitative and qualitative, the variables studied include the validity of the local stories book which was developed through validation by expert experts and practicality based on student questionnaire responses. Based on the research results, it was found that (1) the local stories book validity test by material experts obtained an overall score of 87; (2) media expert aspects of book size, book cover design, and book content design received an overall score of 92; (3) and the practicality test based on the student response questionnaire obtained a score of 88.8. Thus, it is hoped that this research can make a contribution to the field of education and provide solutions that can be used by teachers in facing future learning challengesKeywords: Indonesian Book, Local Stories Book